A Migração Haitiana e a Construção de seus "Nortes": Brasil um "Norte" Alternativo e Temporário - Diémé, Kassoum; Tonhati, Tania Mara Passarelli; Pereda Cordova, Lorena del Pilar (Revista Brasileira de Sociologia - RBS, 2020)
Desde 2010, o número de imigrantes do “Sul Global”no Brasilcresce. A imigração de haitiana, aqui analisada, é caracterizada pelapermanência, circularidade etransitoriedade. Procurado para melhorar de vida, o Brasil é percebidopelos migrantes como umlugardeacumular capitais de mobilidade e expandir acircularidade atéo “Norte Global”. Diante disso, o Brasil se transformouno que Baganha (2002) denomina“uma placa giratória”?Este artigo analisou dados deum projeto de pesquisa do LAEMI(UnB),junto com a UFPR, apoiados pela FAP-DF. A metodologiafoi multisituada, com camposno Brasil eno Haitiem 2018-2019.Observamos queem geral o Brasil é um “Norte Global alternativo” no Sul Global, sendo uma “placa giratória” amenae um “Norte temporário” que tende a se eternizar. Since 2010, Brazil has experienced international migration with greater intensityand complexity. One of the most significant changes faced by the country was the arrival of new migratory flows, especially from Haiti. The Haitian immigration in Brazil has been consolidated and the present study aims to understand: which role Brazil plays in the migratory projects of Haitians? To answer this question, we rely on data from the research named: Immigration and economic crisis: the migratory tac-tics of return and circularity of Haitians. The fieldwork was carried out in Brazil and Haiti, between 2018 and 2019. The results found were that Brazil is seen frequently reported as an “Alternative and Temporary North”, where it is possible to accumulate capital of mobility, education and economic, which allow them expanding their mi-gratory circularity’s horizons.